Deoxycholic acid as a molecular scaffold for tyrosyl-DNA phosphodiesterase 1 inhibition: A synthesis, structure–activity relationship and molecular modeling study - Salomatina, Oksana V.; Popadyuk, Irina I.; Zakharenko, Alexandra L.; Zakharova, Olga D.; Chepanova, Arina A.; Dyrkheeva, Nadezhda.S.; Komarova, Nina I.; Reynisson, Jóhannes; Anarbaev, Rashid O.; Salakhutdinov, Nariman F.; Lavrik, Olga I.; Volcho, Konstantin P. (Steroids, 2021)
[Display omitted] •para-Bromoanilides of deoxycholic acid derivatives were designed and synthesized.•All target compounds were evaluated as inhibitors of Tdp1.•Cytotoxicity against human cancer cell lines (HCT116, HepG2 and A549) was studied.•3,12-Dimethoxy para-bromoanilide 17 is a lead compound (IC50=0.27 μM and CC50>100). Para-Bromoanilides of deoxycholic acid with various functional groups on the steroid scaffold were designed as promising tyrosyl-DNA phosphodiesterase 1 (Tdp1) inhibitors. Tdp1 is a DNA repair enzyme, involved in removing DNA damage caused by topoisomerase I poisons; an important class of anticancer drugs. Thus, reducing the activity of Tdp1 can increase the efficacy of anticancer drugs in current use. Inhibitory activity in the low micromolar and submicromolar concentrations was observed with 3,12-dimethoxy para-bromoanilide 17 being the most active with an IC50 value of 0.27 μM. The activity of N-methyl para-bromoanilides was 3–4.8 times lower than of the corresponding para-bromoanilides. Increased potency of the ligands was seen with higher molecular weight and log P values. The ligands were evaluated for their cytotoxic potential in a panel of tumor cell lines; all were nontoxic to the A549 pulmonary adenocarcinoma cell line. However, derivatives containing a hydroxyl group at the 12th position were more toxic than their 12-hydroxyl group counterparts (acetoxy-, oxo- and methoxy- group) against HCT-116 human colon and HepG2 hepatocellular carcinomas. In addition, an N-methyl substitution led to an increase in toxicity for the HCT-116 and HepG2 cell lines. The excellent activity as well as low cytotoxicity, derivative 17 can be considered as a lead compound for further development.